MOTIVATION RECOMPOSITION : DEFINITION, ORIGINE, ET FONCTIONNEMENT MOTIVATION REDIAL DEFINITION, ORIGIN, AND OPERATION - Medjahdi, Abla (International Journal of Psychosocial Rehabilitation, 2022)
The objective of this article is to give answers deepened(fathomed) on the concept of motivation, to look more specifically on the origin, for the functioning of the concept and its application in the middle of work, that is at the levels of companies. The concept of motivation as object of search(research) concerns of numerous disciplines, it is the subject which enters as study several fields of investigations, the concept establishes(constitutes) a jungle of theories. Whether it is in terms of need, of objectives, expectations(waits), valuable purposes or other the motivation changed many of its meaning since the first initiation of the 50s when gave Abraham Maslow, The objective thus is to answer questionings always put on the understanding of the motivation, mixed(involved) with many more phenomena of searches(researches), and other demonstrations(appearances) which are bound(connected) to him(her) such the job satisfaction.... The study presents a prospect (perspective) to make clarify the understanding on the phenomenon of motivation, it is brought back(reported) according to a new explanatory approach.